Does Information Asymmetry matter in emerging markets?. Evidence from six Latin American stock markets (2011)
Does informed trading affect emerging stock markets? Market microstructure literature establishes that information asymmetry reduces liquidity and moves prices in the direction of the trade. We test for this theoretical implication by running the dynamic PIN model of Easley, Engle, O’Hara y Wu (2008), for stocks of Argentina, Brazil, Chile, Colombia, Mexico and Peru. We use panel data models to test for the relation between PIN, as a measure of information asymmetry, bid-ask spreads, as a measure of liquidity, and returns. The reported results confirm the mentioned theoretical implications, the empirical validity dynamic PIN model, and contribute to a better understanding of price formation in emerging markets.